The statistics of low frequency radio interference at the Murchison Radio-astronomy Observatory - Sokolowski, M.; Wayth, Randall; Lewis, M. (2016)
We characterize the low frequency radio-frequency interference (RFI) environment at the Murchison Radio-astronomy Observatory (MRO), the location selected for the low-frequency component of the Square Kilometre Array. Data were collected from the BIGHORNS instrument, located at the MRO, which records a contiguous bandwidth between 70 and 300 MHz, between November 2014 to March 2015 inclusive. The data were processed to identify RFI, and we describe a series of statistics in both the time and frequency domain, including modeling of the RFI occupancy and signal power as a series of distribution functions, with the goal of aiding future scientists and operation staff in observation planning.